Improving Students’ Vocabulary Retention by Local Culture-Based Material - Raihana, Ilma; Nurkhamidah , Neni (UPT. Pengembangan Bahasa IAIN Zawiyah Cot Kala Langsa, 2022)
The objective of the study is to find out how the local culture-based material is being implemented in the class as well as the effect of implementing local culture-based material in improving the rural coastal area of Riau students’ vocabulary retention. This study was conducted using Classroom Action Research (CAR) method which utilized four phases according to Kemmis and McTaggart model which included planning, action, observation, and reflection. The subject of the study was 27 students from a second-grade classroom in Sains Tahfizh Islamic Center Siak Elementary School. For the data analysis, the researcher used interview guidelines, observation checklists, field notes, and tests to gain the data. The findings discovered that the implementation of local culture-based material successfully improved students’ vocabulary retention based on all of the subject's scores that reached the minimum criteria standard of 80 in the last post-test compared to the pre-test where a lot of students did not reach the minimum standard of criteria. The study also found that the implementation of local culture-based material brought positive impacts on students’ behavior in the classroom. It developed students’ enthusiasm in learning, increased students’ motivation in vocabulary learning, and improved students’ engagement during the learning activity. This study contributed on finding the impact of local culture-based material which benefited the teachers especially in the rural coastal area of Riau, students, and also future researchers.